Quality of life and aesthetic results after mastectomy and mammary reconstruction - Marcela Caetano Cammarota; Amanda Costa Campos; Cesar Augusto Daher Ceva Faria; Gabriel Campelo dos-Santos; Leonardo David Pires Barcelos; Ronan Caputi Silva Dias; Fabrício Tavares Mendonça; Jose Carlos Daher (Revista Brasileira de Cirurgia Plástica)
Introduction: Due to the increased incidence of breast cancer, the demand for breast reconstruction has been increasing, along with concerns regarding the satisfaction and quality of life of the patients. Mastectomy can be a traumatic experience, especially when it is perceived as a mutilation, which can impact self-esteem and emotional stability. The BREAST-Q® questionnaire was internationally validated and formulated for the pre- and postoperative assessment of quality of life related to breast reconstruction. This study aimed to evaluate quality of life and aesthetic result satisfaction in patients who underwent breast reconstruction with implants by comparing the period after breast reconstruction with the period before. Method: A retrospective longitudinal observational study was carried out by reviewing the charts of patients who underwent breast reconstruction using silicone or tissue expander implants from January 2014 to December 2016, in association with a cross-sectional study of the Breast-Q® questionnaire and an evaluation of aesthetic results based on photographic analysis before and after surgery. Results: We selected 74 patients who underwent breast reconstruction with implants (79.7% with silicone prostheses and 20.3% with expanders); 95.94% of the reconstructions were immediate, and no particular laterality predominated. We obtained statistical significance in the domains of both breast satisfaction and physical well-being. Most cases were considered satisfactory by the external evaluator. Conclusion: The patients' quality of life in the period after breast reconstruction with breast implants was superior to that in the period prior to the procedure.